Asphaltene Deposition : Fundamentals, Prediction, Prevention, and Remediation - Tavakkoli, Mohammad; Vargas, Francisco M. (Boca Raton, FL : CRC Press, 2018)
"As global consumption of fossil fuels such as oil increases, previously abundant sources have become depleted or plagued with obstructions. Asphaltene deposition is one of such obstructions which can significantly decrease the rate of oil production. This book offers concise yet thorough coverage of the complex problem of asphaltene precipitation and deposition in oil production. It covers fundamentals of chemistry, stabilization theories and mechanistic approaches of asphaltene behavior at high temperature and pressure. Asphaltene Deposition: Fundamentals, Prediction, Prevention, and Remediation explains techniques for experimental determination of asphaltene precipitation and deposition and different modeling tools available to forecast the occurrence and magnitude of asphaltene deposition in a given oil field. It discusses strategies for mitigation of asphaltene deposition using chemical inhibition and corresponding challenges, best practices for asphaltene remediation, current research, and case studies. "--Provided by publisher.
chapter 1 Introduction / M. Tavakkoli F. M. Vargas -- chapter 2 Crude Oil and Asphaltene Characterization / R. Doherty\n * S. Rezaee\n * S. Enayat M. Tavakkoli F. M. Vargas -- chapter 3 Experimental Investigation of Asphaltene Precipitation / A. T. Khaleel F. Wang E. Song M. Tavakkoli F. M. Vargas -- chapter 4 Asphaltene Precipitation Modeling / C. Sisco M. I. L. Abutaqiya F. Wang J. Zhang M. Tavakkoli F. M. Vargas -- chapter 5 Experimental Determination of Asphaltene Deposition / J. Kuang N. Rajan Babu J. Hu A. Chen M. Tavakkoli F. M. Vargas -- chapter 6 Modeling Methods for Prediction of Asphaltene Deposition / N. Rajan Babu P. Lin J. Zhang M. Tavakkoli F. M. Vargas -- chapter 7 Strategies for Mitigation and Remediation of Asphaltene Deposition / J. Kuang A. T. Khaleel J. Yarbrough P. Pourreau M. Tavakkoli F. M. Vargas -- chapter 8 Case Studies and Field Applications / M. I. L. Abutaqiya C. Sisco J. Kuang P. Lin F. Wang M. Tavakkoli F. M. Vargas -- chapter 9 Conclusions, Current Research, and Future Directions / S. Enayat F. Lejarza R. Doherty A. T. Khaleel C. Sisco J. Kuang M. I. L. Abutaqiya N. Rajan Babu M. Tavakkoli F. M. Vargas.
Keywords: Fluid dynamics; Fuel; Power resources